The keeper [videorecording (DVD)] - Rosenmüller, Marcus H., 1973-; Rosenmüller, Marcus H., 1973-; Kross, David, 1990-; Mavor, Freya; Henshaw, John, 1951- (Kino Lorber, 2021)
Follows the story of Bert Trautmann, a German soldier and prisoner of war, who overcomes British prejudice with the help of a rabbi to find fame as a soccer player and fall in love with an English woman.